Hedysarum ketenoglui (Fabaceae-Hedysareae), a new species from southern Turkey - Başköse, İsa; Yaprak, Ahmet Emre; Akyildirim, Berri̇n (Phytotaxa, 2018)
Hedysarum ketenoglui is described as a new species from Gevne Valley in the Hadim district in the province of Konya in Turkey. The diagnostic morphological characteristics and habitus of the new species are illustrated. The new species differs from Hedysarum anatolicum (syn: Sartoria hedysaroides) in the habitus, stem, leaves and the length of the peduncle, the shape of the leaflets, the number of flowers in the inflorescence, and the size of fruit.